Synthesis, thermal properties and rheological behaviors of novel Poly(ethylene glycol) segmented Poly(arylene ether)s. (20th May 2020) - Tseng, Yu-Chao; Hsieh, Yu-Chao; Chin, Nien-Yuan; Huang, Wen-Yao; Hou, Sheng-Shu; Jan, Jeng-Shiung
Abstract: A series of new poly (ethylene glycol) (PEG) segmented poly (arylene ether)s (PAEs), (PEG-PAEs) were synthesized via nucleophilic substitution polycondensation. The prepared PEG-PAEs are thermally stable up to 190 °C, which is dominated by the PEG segments. Their glass transition temperature (Tg ) points are in the range of -10 - 32 °C, which is dictated by the molecular weights as well as the fraction of PEG segments in the structures. And the materials are in an amorphous state due to the steric hindrance imposed by F1 segments. The rheological measurement reveals that the viscoelastic property of the F-PEG1000 and F-PEG2000 can experience a transition from a glassy state to a leather state and then to a rubbery state after applying the time-temperature superposition (TTS) principle. Moreover, a decreased trend of the complex viscosity is found as the temperature increases, which can be attributed to the accelerated movement of polymer chains at a higher temperature. And the fraction of the PEG segments as well as the molecular weights of the materials can also affect the complex viscosity. Accordingly, the thermal properties and rheological behaviors of the PEG-PAEs can be adjusted by selecting different PEG macromonomers. Graphical abstract: A series of new poly (ethylene glycol) segmented poly (arylene ether)s were synthesized through nucleophilic substitution polycondensation. The results reveal the feasibility of adjusting their thermal properties and rheological behaviors by selecting different PEG macromonomers. Image 1 Highlights: New poly (ethylene glycol) segmented poly (arylene ether)s were synthesized using nucleophilic substitution polycondensation. All polymers are thermally stable up to 190 C and their Tg was related to the selected PEG macromonomers. The polymers can exhibit the transition from a glassy state to a leather state and then to a rubbery state.